High Temperature Processing of Fish Sausage III - Studies on Some of the Storage Characteristics - VICTOR RAJ, M. CROSS; CHANDRASEKHAR, T. C. (Fishery Technology, 2017)
The proximate compos1t1on of the high temperature processed fish sausage was found to be 14.56 % protein, 4.65 % fat, 69.14 % moisture, 2.12 % ::i.sh and 8.12 % carbohydrate. The quality of the product during storage was assessed on the basis of the changes observed in the physical, chemical and microbiological parameters. The results of the different tests such as pH, volatile base nitrogen (VBN), trimethyl amine nitrogen (TMA-N) and jelly strength are summarised and discussed. The total bacterial load increased gradually during storage but was not proportional to the initial load.